COST ANALYSIS AND PROFIT CALCULATION OF CV LUMINTU: A BATIK MANUFACTURING CASE STUDY IN PEKALONGAN - Faikar, Fahd; Kitri, Mandra Lazuardi (Journal of Business and Management, 2018)
Abstract. Background : In many parts of Indonesia, many small and medium-sized manufacturing industries are the main source of livelihood for the population. Not a few of them are out of business because they are not able to sustain their lives every month (Rayadiani, 2015). In Pekalongan, the city is very famous for its batik is a lot of textile industry manufacturing woven fabric ATBM (Investor Daily, 2018) (Non-Woven Weaving Machine) and traditional batik is still able to survive by relying on uniqueness that cannot be duplicated by modern machines (Wiji, 2013). CV. Lumintu is a small-scale manufacturing medium size saw and the production produced is not bulk and not quite customized. Lumintu Workshop is owned by R Asyfa Fuadi. In addition to producing batik orders, R Asyfa Fuadi also sells batik products in a shape of fabric sheets with a fairly easy motive through a network of batik traders in Pekalongan and distributed almost throughout Indonesia. Problem: In this case, many manufacturing firms, let alone with traditional and small scale, do not have a good accounting and financial recording system. Rewards (pricing) made only on the basis of costs incurred for the product alone or guessing because of the absence of good calculations in the cost line. CV. Lumintu only records costs by guesswork only. With conditions that occur, the calculation of prices and profits are almost certainly wrong and can be one of the main causes almost bankruptcy of this traditional company. By doing cost analysis in this traditional manufacturing industry, the author can know and classify all expenses incurred during business process run by CV. Lumintu in everyday life. Apart from calculating the cost incurred, the author can also calculate and know the unit cost and also calculate the breakeven point of each product produced by CV. Lumintu. Methodology: The data collection will be done through the quantitative methodology. In this step, the researcher will have the calculation. Quantitative Research is the methodical correct examination of unmistakable ponders by methods for genuine, logical or computational strategies (Given, 2008). The data collection gained from the primary and secondary data, the primary data from CV. Lumintu which is from the owner itself, and secondary data woud be gained and used as a benchmark to the primary data. Result:The result of this research are (1) the old unit cost is Rp 61.762.233 and the new unit cost is Rp 66.693.394; (2) net income after tax is Rp. 73,548,030, and; (3) a new model of financial statement has to be made by CV Lumintu.Key words: Batik, Manufacturing, Financial Statement, Cost Analysis, Profit Calculation